Broadly neutralizing antibodies suppress HIV in the persistent viral reservoir - Chun, Tae-Wook (Proc Natl Acad Sci U S A, 2014)
Several highly potent and broadly neutralizing monoclonal antibodies against HIV have recently been isolated from B cells of infected individuals. However, the effects of these antibodies on the persistent viral reservoirs in HIV-infected individuals receiving antiretroviral therapy (ART) are unknown. We show that several HIV-specific monoclonal antibodies—in particular, PGT121, VRC01, and VRC03—potently inhibited entry into CD4(+) T cells of HIV isolated from the latent viral reservoir of infected individuals whose plasma viremia was well controlled by ART. In addition, we demonstrate that HIV replication in autologous CD4(+) T cells derived from infected individuals receiving ART was profoundly suppressed by three aforementioned and other HIV-specific monoclonal antibodies. These findings have implications for passive immunotherapy as an approach toward controlling plasma viral rebound in patients whose ART is withdrawn.